Identifying the Income-Poor: Some Controversies in India and Elsewhere - Sreenivasan Subramanian (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
Conventional approaches to the measurement of income-poverty require the ability to identify the poor by reference to a specified poverty line. On the face of it, it may appear to be unproblematic to specify such a poverty line. There are, however, analytical and conceptual difficulties entailed in the identification exercise of poverty measurement, and many of these difficulties have to do with the determination of the appropriate space in which to seek invariance of the poverty standard in terms of which poverty comparisons can be effected. These conceptual niggles have been a feature of the actual experience of the evolution of money-metric poverty lines in concrete historical settings. This essay reviews and critically interprets the Indian experience of poverty estimation with specific reference to the identification problem as it has been addressed in the country in the last fifty or so years. The essay also briefly engages with aspects of the record, in this regard, of the United States Federal Government's poverty thresholds and the World Bank's international poverty lines. An attempt is made to locate the analytical basis of the conceptual difficulties informing the identification exercise, and to relate this to the confusions and controversies that have attended many of the actual efforts in India and elsewhere to assess the magnitudes, spatial distribution, and temporal trends of money-metric poverty. Finally, the essay also advances an alternative practical proposal for the measurement of poverty which avoids the identification exercise altogether, and incorporates within itself aspects of the notions of both relative inequality and inclusive growth. This approach is certainly not exempt from conceptual difficulties of its own. It is, nevertheless, worth asking if the directness and simplicity of this alternative prescription, combined with the conceptual and practical difficulties which also inform the conventional approach to the identification problem, may constitute grounds for submitting the proposal to at least a preliminary consideration. It remains to add that this essay draws very heavily on earlier work done by the author on its subject of enquiry.
Keywords: D30; I30; I32; O15; 330; money-metric poverty line; resources; capabilities; evolution of Indian poverty line; US poverty thresholds; the World Bank poverty line; alternative approach to measuring poverty; quintile income